Setal development and antennular chemosensitivity in blue swimming crab Portunus pelagicus larvae - Ledesma, Anne Brigette B. (University of the Philippines Visayas, 2020)
The antennular morphology and ability of hatchery-reared blue swimming crab Portunus pelagicus larval stages to assess and respond to various chemical odors were evaluated in this study. Morphological analysis of crab larvae during ontogeny shows that the advancement of setae coincides with the development of crab into five larval stages. Six types of seate have been identified: 1) aesthetascs, 2) simple, 3) plumose, 4) plumodenticulate 5) serrate, and 6) pinnatifid setae in the selected chemosensory and mechanosensory appendages. Results revealed that major transformation on the chemomechanosensory appendages during the development of crab larvae occurred in the antennules. This involved a change from a uniramous (zoea) to a three-segmented (megalopa) antennular structure. The abundance of chemoreceptors or aesthetascs over other setal types both in zoea (72%) and megalopa (~33%-37%) antennules was evident thus, implying the significant role and influence of antennules on the sensitivity of crab larvae in odor discrimination. Behavioral tests were further conducted to examine the ability of blue swimming crab larvae to detect novel chemical cues: 1) oyster odor, 2)snapper odor, 3) oyster-snapper odor combination, 4) odor from an injured conspecific, and 5) seawater as control. Results suggest that zoea I larvae (about 1 day old) were not as active in food searching than the later larval stages. Blue swimming crab as young as 2-3 days old (zoea II) had the capability to detect novel odor cues and manifested food search behavior (p,0.05). When presented with a chemical stimulus from snapper, zoea III larvae displayed decreased movement in locating the odor source (p.0.05) but reacted otherwise when the snapper odor was mixed with the oyster cue. In contrast, Zoea IV and megalopa stages wee highly responsive and can distinguish various chemical cues, exhibiting high preference to oyster odor and avoidance reaction to snapper, combined oyster-snapper, and injured conspecific odors (p<0.05). These findings show the importance of chemical signals among decapod crustaceans - how their varying morphological and ontogenetic structures affect their decision-making when confronted with diverse and/or novel odor cues. Results of this study have valuable applications in larval rearing of blue swimming crab for aquaculture, resource restocking, and sea ranching.